DETERMINANTS OF WASTING AMONG UNDER 5 YEARS IN TIMOR LESTE (DHS PROGRAM ANALYSIS 2016) - Rahmatika, Auni; Mahmudiono, Trias; Mahmudah, Mahmudah; Melaniani, Soenarnatalina; Soares, Ivo Da Costa (Universitas Airlangga, 2023)
One of the countries in Asia that has a high prevalence of wasting is Timor-Leste. The prevalence of wasting in Timor-Leste is 24% in children aged 15-49 months. The purpose of this study is to identify the factors that influence the incidence of wasting in children aged 15-49 months in Timor Leste. This research is an analysis of secondary data from the 2016 Demographic and Health Survey (DHS) in Timor-Leste using a cross-sectional approach. Informants in this study were mothers of toddlers aged 15-49 years and had toddlers aged 15-49 months. the number of samples in this study were 1,207 mothers. Bivariate analysis was performed by Chi-Square test and multivariate test by logistic regression test. The results showed that the factors that influence wasting are low birth weight, history of breastfeeding and mother's education level. Meanwhile, after being analyzed using logistic regression, the most influencing variables were low birth weight babies with a significant value of 0.028 and an OR value of 0.620.